Associations Between Children’s Media Use and Language and Literacy Skills - Dore, Rebecca A.; Logan, Jessica; Lin, Tzu-Jung; Purtell, Kelly M.; Justice, Laura M. (Frontiers in Psychology, 2020)
Media use is a pervasive aspect of children’s home experiences but is often not considered in studies of the home learning environment. Media use could be detrimental to children’s language and literacy skills because it may displace other literacy-enhancing activities like shared reading and decrease the quantity and quality of caregiver-child interaction. Thus, the current study asked whether media use is associated with gains in children’s language and literacy skills both at a single time point and across a school year and whether age moderates any association. Children (N = 1583) were from preschool through third grade classrooms and language and literacy skills were measured in the fall and spring of the school year. Parents reported how much time their child spends using media on a typical school day. Regression analyses showed that using 4 hours or more of media was related to lower literacy gains, but not to language gains. Multilevel models conducted as a robustness check showed that this effect did not hold when accounting for classroom. In neither set of models was there an interaction between age and media use. Single-time-point models did show some associations that did not manifest in more stringent models, highlighting the limitations of correlational designs that do not have measures of children’s skills over time. Given the concern and popular press coverage around children’s media use, it is important to acknowledge nonsignificant effects in this domain. These nonsignificant associations suggest that societal fears around children’s media use may be exaggerated. Notably, however, characteristics of children’s media use, like educational content or adult co-use, may moderate any effects. The relation between media use and language and literacy growth did not differ across the age range investigated suggesting that, within this range, younger children are not more vulnerable to detrimental effects.